PENINGKATAN HASIL BELAJAR PAI MATERI HUKUM BACAAN TAJWID MELALUI METODE THINK TALK WRITE (TTW) BERBANTUAN WHATSAPP - Tutiyati, Tutiyati (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2022)
The low student learning outcomes because teachers in learning have not used varied methods. The TTW (Think Talk Write) method is a learning solution that starts with thinking (Think), the results of thinking are communicated with presentations, discussions (Talk) and making a report on the results of the presentation (Write). The purpose of the study was to find out the TTW method assisted by Whatsapp in improving PAI learning outcomes for recitation law materials and how much improvement in student learning outcomes in class XI MIPA 1 Semester 2 of the 2020/2021 academic year. The type of research used is quantitative based on students' pre-test and post-test scores. The data collection method used an essay of 20 questions via WhatsApp. The analysis technique uses the N Gain test to determine the increase in PAI learning outcomes for recitation law materials. The results of the analysis of the pre-test and post-test scores, the percentage of students' completeness in knowledge competence by learning the TTW method assisted by WhatsApp showed an increase. A total of 13 students did not complete the pre-test results with an average of 67 and completeness 57%, meaning that there were 17 students who could achieve completeness in the recitation material. Meanwhile, in the post-test there was an increase in mastery scores, there were 23 students who completed and the average post-test score of students was 76. The percentage of students' completeness in the post-test was 77%. The results of the N Gain analysis increased by 83%, with an N-Gain score of 0.39 in the medium category.